Are First-Mover Advantages Really Sustainable? A Case Study of Foreign Mobile Phone Manufacturers in China - YANG, YU-FANG (2008)
The answer to whether the first-mover advantage is a source of sustainable competitive advantage is still debatable. Empirical studies are widely made in many industries. However, many of them are made in the United States. In this dissertation, the first-mover advantages and the resource-based view of a firm are applied jointly to China's mobile phone industry to examine whether the first-mover advantages are really sustainable.